History of rehabilitation medicine as a medical specialty in the Netherlands - Peek, William J (Acta Fisiátrica, 1998)
In the Netherlands rehabilitation medicine is registered as a medical specialty since 1955. Like in many other countries, at the end of World War II and in the first years afterwards rather suddenly physical medicine and rehabilitation became an important part of medical cure and care and got much attention from military, governamental and medical authorities.